Correlative Analysis Between Serum Anti-mullerian Hormone Concentration and LH:FSH Ratio as Women’s Age Advances: A Hospital-based Study - Mallick, Ram Lala; Kafle, Santosh Upadhyay; Dahal, Prerana; Karna, Tapeshwar Lal; Thakur, Asmitanand (Birat Journal of Health Sciences, 2019)
Introduction: A term ’ovarian reserve’ is described as quantity of ovarian follicular cohort and quality of oocytes. The assessment of an individual’s ovarian reserve comprises evaluation of certain variables like age, follicle stimulating hormone, leutinizing hormone, LH:FSH ratio and prolactin as main task. Recently, scientists have reported anti-mullerian hormone as potential test for ovarian reserve. Recently, it is observed that higher levels of AMH correlate positively with greater number of oocytes with then the improved embryo morphology in in vitro fertilization (IVF) cycles. However, controversy still exists between correlation of AMH and other hormonal tests. Objectives: To investigate correlation of AMH, FSH, LH, LH:FSH ratio and PRL in women who attended the local hospital. Methodology: Venipuncture was performed to collect venous blood samples (n=110) under informed written consents. Following separation of sera, circulating levels of AMH was carried out by ELISA and assessment of FSH, LH and PRL were done using Dry chemistry immunoassay analyzer. Data were analyzed using SPSS software version 16. Results: Our data demonstrated for existence of significant negative correlation between serum LH:FSH ratio and age. Here, the pattern of changes was in accordance to that of serum AMH concentration. So when we compared serum AMH concentrations with values of LH:FSH ratio in relation to age, the existence of a significant correlation was observed. Further, our findings demonstrate a degree of variations among other variables (such as LH, FSH and Prolactin) and are imperative in analytical point of view. Conclusion: Our findings behind significant correlation between serum LH:FSH ratio and AMH level suggest that LH:FSH ratio can be a marker for ovarian reserve and applied to clinical evaluation with AMH for diagnostic purpose.